PENGUJIAN KUAT TARIK PRODUK CETAK 3D PRINTING MATERIAL ABS - Yogie Pranata; Hasdiansah Hasdiansah; Yang Fitri Arriyani (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
3D printing technology is an additive manufacturing technology (layer by layer) to create 3D objects with melted filament material. With this 3D printer, users can create a ready-to-use product. This research uses ABS (Acrylonitrile Butadiene Styrene) filament because mechanically this filament is very strong and has resistance to high temperatures. This study aims to find the highest tensile test value from 3D printer printing results with ABS filament specimens, for the factors used are infill layer thickness, wall printing speed, nozzle temperature, bed temperature, print speed, fan speed, infill density, wall thickness, top layers, bottom layers, infill overlap, retraction distance, and retraction speed. Printing is done with the Anycubic 4Max 3D printing machine, while the specimen size is 115 mm x 19 mm x 4 mm. This study uses the Taguchi L16 method with 13 factors and 2 levels printed as many as 48 specimens. So that the tensile test results were obtained with the highest value of 30.46 MPa in the second experiment the lowest with a value of 25.31 MPa in the third experiment. For the calculation of the S/N ratio, the most influential factor is the fan speed.